Developmental genetics of endometriosis - Baranov, Vladislav S. (Henry Stewart Talks, 2018)
Basic theories & hypotheses on endometriosis, A systems genetic view of endometriosis, The junctional zone and its association with endometriosis, Genomics of endometriosis, The developmental genetic program of endometriosis (EMDP), Critical periods (CP) I, II, and III of EMDP, Implications of the EMDP hypothesis, Validating the EMDP hypothesis